HUBUNGAN PELAYANAN KEPERAWATAN BERBASIS SPIRITUAL DENGAN KEPUASAN KERJA PERAWAT DI RUANG RAWAT INAP RSU GMIM PANCARAN KASIH MANADO - Talibo, Norman Alfiat (JURNAL KESEHATAN KARTIKA, 2024)
Background The level of nurse satisfaction greatly influences the performance of nurses in implementing nursing services in hospitals. Spiritually based nursing services are one of the factors in nurses' job satisfaction. The aim of this research was to determine the relationship between spiritually based nursing services and job satisfaction of nurses in the inpatient ward at the GMIM Pancaran Kasih General Hospital, Manado. This research uses a descriptive analytical method with a cross sectional design. The sample was taken based on the number of respondents as many as 33 people using total sampling techniques. Data collection was carried out using a questionnaire. Next, the data were analyzed using the Chi-Square Statistical Test with a significance level of α ≤ 0.05. The results of the research obtained a value of p = 0.000 (α ≤ 0.05), meaning that there is a relationship between spiritual-based nursing services and job satisfaction of nurses in the inpatient room at the GMIM Pancaran Kasih General Hospital, Manado.The conclusion in this study is that there is a relationship between spiritual-based nursing services and job satisfaction of nurses in the inpatient wards at the GMIM Pancaran Kasih General Hospital, Manado. It is hoped that the suggestions will become evaluation material for the future in order to create high-quality nursing services.